2020
DOI: 10.1080/13600818.2020.1837093
|View full text |Cite
|
Sign up to set email alerts
|

Vigilante youths and counterinsurgency in Northeastern Nigeria: the civilian joint task force

Abstract: Building on the broader literature on vigilantism, communal war and conflict, this paper examines why and how the Civilian Joint Task Force (CJTF) in northeastern Nigeria mobilized into a pro-government militia with the aim of extirpating Boko Haram insurgents, sponsors and supporters from their communities. It provides a rich and diverse empirical evidence and analysis of why and how local youths joined the CJTF, its modus operandi, and the nature of its relationship to the military and local populations. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…It has been argued that state vigilantism can be said to have five defining features relating to the intensity of violence, the dehumanisation of the target group, the involvement of the state apparatus in killings, the denial of involvement of the state and the vigilante form of the killings themselves. Whilst the cases here are drawn from Southeast Asia, this model of state vigilantism could be applied to various other contexts where vigilante forces blur the line between state and autonomous citizens, such as with Nigeria's Civilian Joint Task Force (Agbiboa, 2020) and death squads in the Brazilian context (Scheper-Hughes, 2015). This paper has also demonstrated that whilst the intent of state vigilantism is to give the impression of autonomous citizens reacting to crime within society, there is a significant body of evidence to show that the state is complicit in such activities.…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that state vigilantism can be said to have five defining features relating to the intensity of violence, the dehumanisation of the target group, the involvement of the state apparatus in killings, the denial of involvement of the state and the vigilante form of the killings themselves. Whilst the cases here are drawn from Southeast Asia, this model of state vigilantism could be applied to various other contexts where vigilante forces blur the line between state and autonomous citizens, such as with Nigeria's Civilian Joint Task Force (Agbiboa, 2020) and death squads in the Brazilian context (Scheper-Hughes, 2015). This paper has also demonstrated that whilst the intent of state vigilantism is to give the impression of autonomous citizens reacting to crime within society, there is a significant body of evidence to show that the state is complicit in such activities.…”
Section: Discussionmentioning
confidence: 99%
“…The case study was conducted in Yobe State of northeast Nigeria. The State is among the three (Borno, Adamawa, and the Yobe States) worse affected by the Boko Haram rebellion (Agbiboa, 2020). It is also a home for the two most ranked spiritual leaders (Mohammed Yusuf and Abubakar Shekau) of the movement.…”
Section: Methodsmentioning
confidence: 99%
“…Acquainted with their technical knowledge of the physical terrain such the hills, mountains, creeks, and forests in the northeast combined with their knowledge of the Boko Haram fighters and collaborators, the militias appeared instrumental in weakening the Boko Haram hostilities. Agbiboa (2020) submitted that the militias are the bridgebuilder between the soldiers, whose members' are alien to the region, and the civilians that are suspicious toward the existence of the military in their communities. Therefore, the militia besides being brokers of peaceful existence, are instrumental for harnessing critical, accurate, and timely intelligence about the insurgents' movements, their hideouts, and supplies routes while sharing same with the soldiers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, the STTEP approach also worked closely with local citizen militias known as the Civilian Joint Task Force (CJTF). The CJTF, which was established by Borno State in June 2013 and now includes thousands of volunteers, is seen as a valuable force multiplier by the Nigerian security forces, although there has been frequent tension between the CJTF and the security forces due to police and military brutality against the vigilantes (Agbiboa, 2020). Recognizing this divide and the utility of the local military for intelligence, translation, support, and local acceptance, the STTEP approach overcame these tensions by encouraging cooperation between uniformed forces and citizen militias in their operations to combat Boko Haram.…”
Section: Insights Into Regional Developmentmentioning
confidence: 99%